AB0761 TNF inhibitors for the treatment of ANCA associated vasculitis: A systematic review. (23rd January 2014) - Silva, L.; Blanco, R.; Martínez-Taboada, V.; Loza, E.; Pego, J.M.; Rúa-Figueroa, I.; Muñoz-Fernández, S.
Abstract : Background: Cyclophosphamide (CYC) and corticosteroids (CS) are widely used in the treatment of ANCA-associated vasculitis (AAV). However, not all patients achieve remission and these drugs are associated with important adverse events. New treatments like TNF inhibitors have been proposed. Objectives: To systematically review the efficacy and safety of anti-TNF drugs in AAV. Methods: We systematically searched MEDLINE, EMBASE and the Cochrane Central Register of Controlled Trials up to October 2011 using a comprehensive search strategy for anti-TNF drugs, AAV, efficacy and safety (mesh terms and text words). Selection criteria were predefined by protocol. We selected meta-analysis, systematic literature reviews, clinical trials (CT), cohort studies and case series with >3 cases, that included >18 year-old patients with AAV on anti-TNF drugs. Studies including patients with Behçet disease, cryoglobulinemia, large vessel and secondary vasculitis, and basic science studies were excluded. Title and abstract selection and subsequent detailed review of selected articles were independently performed by two reviewers. The included studies quality was graded using the Oxford Levels of Evidence Scale, and results expressed as level of evidence (LE), recommendation grade (RG). Results: The search strategy identified 2, 762 potentially relevant articles, of which 80 were selected for full paper review and eventually 12 were selected for the analysis. The selection included 2 randomized CT, 3 open trials, 1 case-control study, 1 cohort study and 4 case series, which analyzed 328 patients. Studies main characteristics and results are shown in the table. Conclusions: Infliximab is not more effective than CYC regarding remission induction in AVV patients (LE 1b; GR A), although is effective as steroid-sparing agent (LE 1b; GR A). Etanercept is not effective to maintain remission in patients with Wegener's granulomatosis (LE 1b; GR A) and serious adverse events have been reported especially solid cancers. The addition of adalimumab to CS and CYC in severe AAV patients is associated with response rates and adverse events similar to CS and CYC but reduced CS exposure (LE 2b; GR B). Disclosure of Interest: None Declared